Antenatal and Neonatal Antecedents of Executive Dysfunctions in Extremely Preterm Children. (March 2018) - Leviton, Alan; Joseph, Robert M.; Allred, Elizabeth N.; O'Shea, T. Michael; Taylor, H. Gerry; Kuban, Karl K. C.
To find out why children born extremely preterm are at heightened risk of executive dysfunctions, the authors assessed 716 children who were 10 years old born extremely preterm whose IQ was ≥ 70. A working memory dysfunction (n = 169), an inhibition dysfunction (n = 360), a switching dysfunction (355), and all 3 (executive dysfunction; n = 107) were defined on the basis of Z-scores ≤ –1 on the Differential Ability Scales–II Working Memory composite, and/or on the NEPSY-II Inhibition-Inhibition and Inhibition-Switching subtests. All risk profiles include an indicator of socioeconomic disadvantage. The risk profile of each of the 3 individual dysfunctions includes an indicator of the newborn's immaturity, and the risk profiles of the inhibition dysfunction and switching dysfunction also include an indicator of inflammation. Only the switching dysfunction was associated with fetal growth restriction. The risk factors for executive dysfunction can be subsumed under the 4 themes of socioeconomic disadvantage, immaturity/vulnerability, inflammation, and fetal growth restriction.